Learn To Read Write the Qur'an: Does It Really Improve Spiritual Intelligence - Rani Puspita; Wahyuni Sari; Imam Tabroni (Kampret Journal, 2023)
The purpose of this study is to determine the spiritual intelligence of children which is processed through reading and writing the Qur'an. Is this factor directly obtained by children when learning or is there a factor of inclusion from the teacher in this increas. Methods naturally use qualitative. Take a full photo of this activity naturally. The results of the study show that spiritual intelligence is intelligence obtained through an integrated program with the al-Qur`an reading and writing program. Learning like this gives a spiritual touch if children are not only given knowledge about hijaiyah letters, but also the benefits of learning the Qur'an and its impact on children in this world and the hereafter. Teachers often give this motivation during learning. The teacher asks parents to establish good communication to jointly develop children's potential, namely the ability to perform the five daily prayers with good reading, pray every time and have done something, and recite the Qur`an at home as much as possible. This series gives children a spiritual touch that is integrated with learning the Qur'an.